Bioactive Natural Antivirals: An Updated Review of the Available Plants and Isolated Molecules - Mohan, Syam (Molecules, 2020)
Viral infections and associated diseases are responsible for a substantial number of mortality and public health problems around the world. Each year, infectious diseases kill 3.5 million people worldwide. The current pandemic caused by COVID-19 has become the greatest health hazard to people in their lifetime. There are many antiviral drugs and vaccines available against viruses, but they have many disadvantages, too. There are numerous side effects for conventional drugs, and active mutation also creates drug resistance against various viruses. This has led scientists to search herbs as a source for the discovery of more efficient new antivirals. According to the World Health Organization (WHO), 65% of the world population is in the practice of using plants and herbs as part of treatment modality. Additionally, plants have an advantage in drug discovery based on their long-term use by humans, and a reduced toxicity and abundance of bioactive compounds can be expected as a result. In this review, we have highlighted the important viruses, their drug targets, and their replication cycle. We provide in-depth and insightful information about the most favorable plant extracts and their derived phytochemicals against viral targets. Our major conclusion is that plant extracts and their isolated pure compounds are essential sources for the current viral infections and useful for future challenges.